2022
DOI: 10.1007/s11947-021-02752-6
|View full text |Cite
|
Sign up to set email alerts
|

Power Ultrasound-Assisted Impregnation of Apple Cubes with Vitamin B12

Abstract: This work explores the use of ultrasound (US) as a means of intensifying the impregnation of apple cubes with vitamin B12 (cyanocobalamin). The effect of different US power densities (90 and 200 WL−1) and treatment times (5, 10, and 15 min) was evaluated, on vitamin load, vitamin stability, and physicochemical and microstructural properties of the fruit matrix. The US enhanced the impregnation producing high cyanocobalamin content products (0.12–0.19 mg vitamin/g db.). Vitamin losses in the sonication medium d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The intensification of water transfer from a hypotonic solvent into vegetable cells because of US application has already been reported by other authors. For instance, Vasile et al [8] , who subjected apple samples to an immersion treatment in water enriched with cyanocobalamin, observed a water gain with US application (200 W/L for 15 min) larger than that observed without US. Among the three investigated materials, apple was the most affected when using water as an immersion medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensification of water transfer from a hypotonic solvent into vegetable cells because of US application has already been reported by other authors. For instance, Vasile et al [8] , who subjected apple samples to an immersion treatment in water enriched with cyanocobalamin, observed a water gain with US application (200 W/L for 15 min) larger than that observed without US. Among the three investigated materials, apple was the most affected when using water as an immersion medium.…”
Section: Resultsmentioning
confidence: 99%
“…This type of ultrasound has high intensity (10–1000 W/cm 2 ) and low frequency (20–100 kHz) [4] and has been applied to numerous unit operations in the food industry. These operations include extraction [5] , [6] , osmotic dehydration [7] , impregnation [8] , drying [9] , emulsification [10] , defoaming [11] and so forth. US has also been applied as an immersion pre-treatment for further processes such as drying [12] , hydro distillation of essential oil [13] , physicochemical modification of starches [14] and others.…”
Section: Introductionmentioning
confidence: 99%
“…Irazoqui et al [33] observed such an effect on lettuce surfaces. On the other hand, Vasile et al [34] noted that a significant increase in water content was lacking (mass of samples) in apple tissue during ultrasound-assisted impregnation using a hypotonic solution containing vitamin B12. Substantial simultaneous impregnation of the tissue with vitamin B12 was found.…”
Section: Resultsmentioning
confidence: 99%